2017
DOI: 10.1080/13102818.2016.1277956
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and biological activities of various extracts from Rosa sempervirens leaves

Abstract: Rosa sempervirens L. (Rosaceae) growing wildly in Turkey is used in folk medicine for various indications. Here, we report the isolation of four flavonoids and determination of the total phenolic and flavonoid contents and the antimicrobial and antioxidant activities of various extracts from R. sempervirens leaves. Antioxidant activity was determined by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS). The total phenolic and flavonoid contents were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
(25 reference statements)
3
19
2
Order By: Relevance
“…Several studies have reported the affinity of Rosa antioxidant activity towards the external and internal factors. According to Bitis et al ., R. sempervirens leaves showed considerable high radical‐scavenging effect (DPPH and TEAC) by their EtOAc extracts. D'angiolillo et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the affinity of Rosa antioxidant activity towards the external and internal factors. According to Bitis et al ., R. sempervirens leaves showed considerable high radical‐scavenging effect (DPPH and TEAC) by their EtOAc extracts. D'angiolillo et al .…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that Rosa species exhibited an important antioxidant power and could be considered a potential solution for the production of natural antioxidants and functional food nutriments. 6,23,39,40 Furthermore, Rosa extract valorisation should make allowance for the ecological variation of plant origins and their influence on phenolic composition and antioxidant abilities. 2,34 This variation could be useful for the choice of suitable species or genotypes in future studies of plant selection.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The large amounts of rose leaves and achenes constituting an interesting raw material for potential application are obtained from rose plantations every year. Although these rose organs are still being treated as plantation by-products and often discarded without any utilization, the interest in their potential use for commercial purposes (e.g., for preparation of nutraceuticals, functional foods, or pharmaceutical products) has continued to grow in recent years [14][15][16][17][18][19][20][21]. Moreover, rose leaves have been used in folk medicine to cure bronchitis and were found to exhibit anti-angiogenic, anti-inflammatory, and anti-nociceptive activities [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The Rosa ( R .) species is widely distributed plants, and is used as a medicinal herb against nephritis and hemorrhoids (Bitis et al., 2017; Caliskan, Aka, & Oz, 2017). Because of the presence of various terpenes (glycosides), flavonoids, and anthocyanins (Knapp et al., 1998; Kumar, Bhandari, Singh, Gupta, & Kaul, 2008; Oka et al., 1998; Schieber, Mihalev, Berardini, Mollov, & Carle, 2005), roses were proposed to display diverse biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…been regarded as good dietary sources owing to their various beneficial elements, such as phenolic acids, flavonols, and anthocyanins (Navarro-Gonzalez et al, 2015); beneficial properties of flowers have been well-defined, including antioxidant properties (Krishnaiah et al, 2011;Kumar et al, 2009;Masek et al, 2017;Mohebitabar et al, 2017). The Rosa (R.) species is widely distributed plants, and is used as a medicinal herb against nephritis and hemorrhoids (Bitis et al, 2017;Caliskan, Aka, & Oz, 2017). Because of the presence of various terpenes (glycosides), flavonoids, and anthocyanins (Knapp et al, 1998;Kumar, Bhandari, Singh, Gupta, & Kaul, 2008;Oka et al, 1998;Schieber, Mihalev, Berardini, Mollov, & Carle, 2005), roses were proposed to display diverse biological activities.…”
mentioning
confidence: 99%